2016
DOI: 10.1038/ni.3348
|View full text |Cite
|
Sign up to set email alerts
|

Blimp-1 controls plasma cell function through the regulation of immunoglobulin secretion and the unfolded protein response

Abstract: Plasma cell differentiation requires silencing of B cell transcription, while establishing antibody-secretory function and long-term survival. The transcription factors Blimp-1 and IRF4 are essential for plasma cell generation, however their function in mature plasma cells has remained elusive. We have found that while IRF4 was essential for plasma cell survival, Blimp-1 was dispensable. Blimp-1-deficient plasma cells retained their transcriptional identity, but lost the ability to secrete antibody. Blimp-1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
349
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 306 publications
(380 citation statements)
references
References 55 publications
(97 reference statements)
21
349
2
1
Order By: Relevance
“…Expression of intracellular factors important for plasma cell survival (such as Irf4, Mcl1, and Hdac11 ) as well as the Atg5 autophagy gene was also affected. Expression of Prdm1 or Xbp1 , which are important to maintain the plasma cell secretory function but dispensable for their survival (40), however, was not affected. To further confirm that Rab7 inhibition directly affects plasma cell survival, we treated CD138 hi cells generated in vitro with CID 1067700.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of intracellular factors important for plasma cell survival (such as Irf4, Mcl1, and Hdac11 ) as well as the Atg5 autophagy gene was also affected. Expression of Prdm1 or Xbp1 , which are important to maintain the plasma cell secretory function but dispensable for their survival (40), however, was not affected. To further confirm that Rab7 inhibition directly affects plasma cell survival, we treated CD138 hi cells generated in vitro with CID 1067700.…”
Section: Resultsmentioning
confidence: 99%
“…Rab7 inhibition reduced expression of several genes instrumental to plasma cell survival, such as Cxcr4 , Irf4 and Mcl1 (40, 46, 47). Expression of CXCR4 (a G protein-coupled receptor) has been shown to be boosted by NF-κB, consistent with the identification of several κB sites in the Cxcr4 gene locus (48), consistent with a role of Rab7 in NF-κB activation and rescue of survival of CID 1067700-treated plasma cells with enforced expression of IKKβ CA .…”
Section: Discussionmentioning
confidence: 99%
“…Tellier et al recently demonstrated that BLIMP1 acts to promote Ig gene transcription, as Blimp1 deletion results in decreased Ig gene expression and, consequently, reduced activation of both mTORC1 and components of the UPR (46). These results further highlight the importance of mTORC1 in the context of immunoglobulin production and long-lived antibody responses, and suggest a model wherein mature plasma cells exploit the TORC1 pathway to optimize antibody synthesis and secretion in response to BLIMP1-driven amplification of Ig gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular drivers of B cell differentiation into the PC fate are better understood, and have been recently reviewed (Kometani et al, 2013; Nutt et al, 2015). Key in this process is the activation of the PC master-regulator Blimp1 ( Prdm1 ) (Turner et al, 1994), which, among many other functions (Minnich et al, 2016; Tellier et al, 2016) helps shut down expression of transcription factors such as Pax5 and Bcl6, responsible for maintenance of B cell and GC identity, respectively [reviewed in (Nutt et al, 2015)]. What signals underlie the decision of activated or GC B cells to switch on Blimp1 is an active area of investigation.…”
Section: Post-gc B Cell Fatesmentioning
confidence: 99%